Trade and development report 2013 - United Nations Conference on Trade; Development (United Nations, 2013)
The shape of the world economy has changed significantly over the last two decades, with a rising importance of several developing countries and regions as additional drivers of global economic growth. The main objective of Trade and Development Report 2013 is to assess the systemic changes in the underlying structure of the world economy and to analyse the resulting policy challenges. Particular attention will be paid to a plausible scenario in which developing and transition countries must design their development strategies in a context of a prolonged period of sluggish growth in developed countries. The Report’s main message will be that in order to achieve high, sustained and inclusive growth, developing and transition economies will need to move towards a new form of development, away from seeking net-export advantages on the back of global imbalances. Rather, the new context calls for strengthening domestic income and demand and reinvigorating regional and South-South coordination and economic linkages.